Mapping current research on biomarkers associated with the diagnosis of pedophilia: a scoping review - Karanikola, Maria; El Riz, Anna T.; Chatzittofis, Andreas (Frontiers in Psychiatry, 2025)
BackgroundPedophilia remains a challenging area of study due to its sensitive nature and the ethical considerations surrounding research involving individuals with deviant sexual interests.ObjectiveThe aim of this review was to systematically explore and present the current research status on biomarkers in pedophilia. The focus was on biomarkers that may support the diagnostic process, treatment evaluation and assessment of risk and recidivism of pedophilia.MethodsBased on literature searches [MEDLINE, EMBASE, Scopus, APA PsycNet, Google Scholar], a scoping review was applied between January and March 2024, including studies in adults diagnosed with pedophilia, published within the last decade.ResultsA total of 39 studies were included in the study sample. These encompassed only male participants. Biomarkers associated with pedophilia were identified and categorized as following: genetic/epigenetic and neuroendocrinal, physiological, cognitive/behavioral, and neuroimaging/neurofunctional. Results indicated the presence of cognitive deficits or impairments, especially in memory and executive functions, significant structural and functional brain differences in neuroimaging, with evidence of altered connectivity, volume reductions, and abnormal brain activation patterns. Physiological biomarkers revealed altered physical traits, attentional control, and sexual arousal patterns in pedophilia, with neural responses suggesting dysfunction in prefrontal cortex and error processing areas. Lastly, genetic and neuroendocrine studies suggested a potential link between epigenetic alterations in the serotonergic and testosterone systems, with lower testosterone levels and signs of prenatal androgen exposure observed in pedophilic individuals.ConclusionsThis review mapped the existing state of the art data in biomarkers in pedophilia, also supporting the existence of promising biological systems implicated in the pathophysiology of pedophilia, thus emphasized the need for further research in the field.Systematic review registrationhttps://osf.io/8v9wn, identifier https://doi.org/10.17605/OSF.IO/8V9WN.